Advances in the theoretical understanding of photon upconversion in rare-earth activated nanophosphors. (7th October 2014) - Liu, Guokui
Abstract : A comprehensive review of the theoretical background is provided for understanding photon upconversion with particular attention to assessing photoluminescence dynamics in rare-earth activated nanophosphors. Abstract : Photon upconversion in rare earth activated phosphors involves multiple mechanisms of electronic transitions. Stepwise optical excitation, energy transfer, and various nonlinear and collective light–matter interaction processes act together to convert low-energy photons into short-wavelength light emission. Upconversion luminescence from nanomaterials exhibits additional size and surface dependencies. A fundamental understanding of the overall performance of an upconversion system requires basic theories on the spectroscopic properties of solids containing rare earth ions. This review article surveys the recent progress in the theoretical interpretations of the spectroscopic characteristics and luminescence dynamics of photon upconversion in rare earth activated phosphors. The primary aspects of upconversion processes, including energy level splitting, transition probability, line broadening, non-radiative relaxation and energy transfer, are covered with an emphasis on interpreting experimental observations. Theoretical models and methods for analyzing nano-phenomena in upconversion are introduced with detailed discussions on recently reported experimental results.